Preparation and application of porous liquid mixed matrix membrane
By covering the ionic liquid on the organic skeleton and closure of polyethamine to form a modified metal organic skeleton with a nuclear-shell structure, the ionic liquid system is formed, and the mixed mixed matrix membrane with the polyether was mixed , Solve the problem of being susceptible to damage and compatibility under high pressure under high pressure, which improves the problem of gaseous separation performance.
Patent Information
- Application Number
- CN202410587925.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-13
AI Technical Summary
In the prior art, zirconium-based metal organic framework membranes are prone to agglomeration in the membrane, resulting in poor compatibility with the polymer matrix, films are prone to damage under high pressure, and carbon dioxide permeability flux is affected by pressure and temperature. big.
By using the metal organic skeleton, the characteristics of the regulatory pores are affected by the temperature, and the ionic liquid is covered on the metal organic skeleton, and the polyethane amine is spread on the surface of the metal organic skeleton in a weak alkali environment to form a nuclear-shell structure The polyetheric amine modified metal organic skeleton covers the ionic liquid system, and then mixed with polyether embedded amine mixed mixed matrix membrane.
This method has increased the spatial block of the surface of the organic skeleton, reducing the reunion of nanoparticles, increasing its dispersality in the polymer matrix, further promoting the spatial stability of the particles, improving the permeability and selectivity of the gas , Alleviate the compatibility and mechanical performance of the membrane.
Smart Images

Figure CN119368016A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane separation, and in particular to a preparation method and application of a porous liquid mixed matrix membrane. Background Art
[0002] The adverse effects of carbon dioxide on the environment are self-evident. However, as an abundant carbon resource, carbon dioxide is widely used in various chemical industries. Therefore, how to efficiently recycle carbon dioxide has become an urgent problem to be solved in today's era. In the existing technology, membrane separation method stands out among many separation methods because of its advantages such as low energy consumption, environmental friendliness and simple equipment. Among them, polyether block amide-1657 has become the most widely used membrane material due to its excellent comprehensive performance and high gas selectivity. However, how to break through the restrictive relationship between permeability and selectivity, that is, the Robers upper limit, has now become a universal standard for evaluating gas separation membranes.
[0003] Metal-organic framework-encapsulated ionic liquid refers to the filling of ionic liquid in metal-organic framework, which increases the adsorption and dissolution capacity of carbon dioxide on the one hand, and reduces the passage of other macromolecular gases on the other hand. Therefore, it has begun to attract widespread attention. At present, zirconium-based metal-organic framework and ionic liquid are often used to modify gas separation membranes; however, zirconium-based metal-organic framework membranes still have problems such as poor mechanical properties of modified membranes, poor compatibility with polymer matrices, easy agglomeration of zirconium-based metal-organic framework membranes in the membranes, easy damage of membranes under high pressure, and the carbon dioxide permeation flux is greatly affected by pressure and temperature. Summary of the invention
[0004] The purpose of the embodiments of the present invention is to provide a method for preparing and applying a porous liquid mixed matrix membrane, so as to alleviate the technical problem existing in the prior art that when zirconium-based metal organic frameworks and ionic liquids are used to modify gas separation membranes, the zirconium-based metal organic framework membranes are prone to agglomeration within the membranes, and therefore, the compatibility between the zirconium-based metal organic framework membranes and the polymer matrix is poor, and the membranes are prone to damage under high pressure.
[0005] To solve the above technical problems, the embodiments of the present invention provide the following technical solutions: The first aspect of the present invention provides a method for preparing a porous liquid mixed matrix membrane, comprising the following steps: S10. Utilizing the property that the metal organic framework can adjust the pore size under the influence of temperature, the ionic liquid is coated on the metal organic framework under the action of the first temperature, and then the polyetheramine is grafted on the surface of the metal organic framework in a weakly alkaline environment to form a polyetheramine-modified metal organic framework coated with an ionic liquid system having a core-shell structure; S20. The polyetheramine-modified metal organic framework-coated ionic liquid system obtained in step S10 is added to the polyether block amide to obtain a casting solution, and then heated and stirred in an oil bath; The uniformly stirred casting solution is poured into a polytetrafluoroethylene plate by a casting method, and after vacuum treatment at room temperature and heating degassing, a required mixed matrix membrane containing polyetheramine-modified metal organic framework-coated ionic liquid and polyether block amide is obtained.
[0006] In some modified embodiments of the first aspect of the present invention, in step S10, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate; 1-octyl-3-methylimidazolium hexafluorophosphate; 1-butyl-3-methylimidazolium tetrafluoroborate; 1-octyl-3-methylimidazolium tetrafluoroborate; The metal organic framework is a zirconium hydroxyphthalate metal organic framework; and the ionic liquid is coated on the metal organic framework to form a zirconium hydroxyphthalate coated ionic liquid system; The polyetheramine is any one of polyetheramine M1000, polyetheramine M600, polyetheramine M2070, polyetheramine D2000, polyetheramine T5000 and polyetheramine T403.
[0007] In some modified embodiments of the first aspect of the present invention, in step S20, the mass fractions of the polyetheramine modified metal organic framework coated ionic liquid system are 0, 1%, 2%, 3%, 4%, and 5%, respectively.
[0008] In some modified embodiments of the first aspect of the present invention, in step S20, the oil bath heating condition is 50-80° C., and the oil bath heating stirring time is 8-16 hours.
[0009] In some modified implementations of the first aspect of the present invention, in step S20, the vacuum pressure of the room temperature vacuum treatment is between 0.01-0.02 MPa, and the vacuuming time is between 20-24 hours.
[0010] In some modified embodiments of the first aspect of the present invention, when the mixed matrix membrane is used for a mixed gas containing carbon dioxide, the transmembrane pressure difference of the mixed matrix membrane is required to be 0.1-0.5 MPa, and the operating temperature is 30-60°C.
[0011] Compared with the prior art, the invention adopts a method of coating ionic liquid with polyetheramine-modified zirconium-based metal organic framework to form a polyetheramine-modified metal organic framework-coated ionic liquid system with a core-shell structure; and blending with polyether block amide to prepare a mixed matrix membrane. Since the polyetheramine is grafted on the surface of the zirconium-based metal organic framework by covalent grafting, the polyetheramine can increase the steric hindrance of the surface of the zirconium-based metal organic framework, reduce the agglomeration of nanoparticles, and improve their dispersion in the polymer matrix, further promote the spatial stability of the particles, improve the gas permeability and selectivity, and alleviate the technical problems of poor compatibility between the zirconium-based metal organic framework membrane and the polymer matrix in the prior art, and easy damage of the membrane under high pressure, thereby achieving the technical effect of inhibiting the agglomeration of the zirconium-based metal organic framework-coated ionic liquid and improving the gas separation performance of the membrane material. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.
[0013] Figure 1 A schematic diagram of a method for preparing a porous liquid mixed matrix membrane and its application provided by an embodiment of the present invention; Figure 2 In a method for preparing a porous liquid mixed matrix membrane and application provided in an embodiment of the present invention, the amine group of the polyetheramine reacts with the hydroxyl group of the metal organic framework to undergo a dehydration reaction; Figure 3 A preparation method of a porous liquid mixed matrix membrane and application requirements provided by an embodiment of the present invention; a comparison chart of the separation performance of the mixed matrix membrane and the Robertson line; Figure 4 A schematic diagram of an experimental process of preparing a porous liquid mixed matrix membrane and using it to separate carbon dioxide gas is provided in an embodiment of the present invention.
[0014] Among them: 1-carbon dioxide cylinder; 2-nitrogen cylinder; 3-methane cylinder; 4-oxygen cylinder; 5-pressure reducing valve; 6-needle valve; 7-control valve; 8-digital pressure gauge; 9-thermostatic box 9; 10-membrane device; 11-pressure relief valve; 12-soap bubble flow meter; 101-metal organic framework; 102-ionic liquid; 103-zirconium hydroxyphthalate coated ionic liquid system; 104-polyetheramine; 105-polyether block amide; 106-polyetheramine-modified metal organic framework coated ionic liquid system; 107-carbon dioxide; 111-monoamine; 112-diamino; 113-triamino; 114-polyetheramine (monoamine) modified zirconium hydroxyphthalate coated ionic liquid system; 115-polyetheramine (diamino) modified zirconium hydroxyphthalate coated ionic liquid system; 116-polyetheramine (triamine) modified zirconium hydroxyphthalate coated ionic liquid system. DETAILED DESCRIPTION
[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0017] like Figure 1 As shown, the present invention provides a method for preparing a porous liquid mixed matrix membrane and its application, comprising the following steps: S10. Utilizing the property that the metal organic framework 101 can adjust the pore size under the influence of temperature, the ionic liquid 102 is coated on the metal organic framework 101 under the action of the first temperature, and then the polyetheramine 104 is grafted on the surface of the metal organic framework 101 under a weak alkaline environment to form a polyetheramine 104 modified metal organic framework coated ionic liquid system 106 having a core-shell structure; S20. The polyetheramine metal organic framework coated ionic liquid system 106 obtained in step S10 is added to the polyether block amide 105 to obtain a casting solution, and then heated and stirred in an oil bath; The uniformly stirred casting solution is poured into a polytetrafluoroethylene plate by a casting method, and after vacuum treatment at room temperature and heating for degassing, a required mixed matrix membrane containing polyetheramine-modified metal organic framework-coated ionic liquid 106 and polyether block amide 105 is obtained.
[0018] The invention adopts a method in which a zirconium-based metal organic framework coated ionic liquid is modified by polyetheramine 104 to form a polyetheramine-modified metal organic framework coated ionic liquid system 106 with a core-shell structure; and the system is blended with polyether block amide 105 to prepare a mixed matrix membrane. Since the polyetheramine 104 is grafted onto the surface of the zirconium-based metal organic framework 101 by covalent grafting, the polyetheramine 104 can increase the steric hindrance on the surface of the zirconium-based metal organic framework 101, reduce the agglomeration of nanoparticles, and improve their dispersion in the polymer matrix, further promote the spatial stability of the particles, improve the gas permeability and selectivity, and alleviate the technical problems in the prior art that the zirconium-based metal organic framework 101 membrane has poor compatibility with the polymer matrix and the membrane is prone to damage under high pressure, thereby achieving the technical effect of inhibiting the agglomeration of the zirconium-based metal organic framework 101 coated ionic liquid and improving the gas separation performance of the membrane material.
[0019] Taking polyetheramine 104D2000 as an example, the synthesis principle and mechanism of other types of polyetheramine 104 (M600, M1000, M2070, T403, T5000) are consistent. The polyether group in polyether block amide 105 (Pebax-1657) has a special affinity for carbon dioxide 107 gas, making carbon dioxide 107 easily adsorbed and dissolved on the membrane surface. 1-Butyl-3-methylimidazolium hexafluorophosphate; 1-octyl-3-methylimidazolium hexafluorophosphate; 1-butyl-3-methylimidazolium tetrafluoroborate; 1-octyl-3-methylimidazolium tetrafluoroborate, the alkalinity is strong, the N atom on imidazole is a Lewis base, and carbon dioxide 107 is a Lewis acid, and there is a Lewis acid-base interaction between the two. The amino group of polyetheramine 104 is a basic group, while carbon dioxide 107 is an acidic gas. The interaction between the two is strong and reversible, which has a good effect on fixing carbon dioxide 107. In addition, the steric hindrance on the surface of zirconium hydroxyphthalate metal organic framework 101 can be increased through repulsive force, effectively preventing the aggregation of zirconium hydroxyphthalate metal organic framework 101.
[0020] It should be noted that if Figure 2As shown, the metal organic framework 101 is a zirconium hydroxyphthalate metal organic framework; and the ionic liquid is coated on the metal organic framework to form a zirconium hydroxyphthalate coated ionic liquid system 103; the ionic liquid is coated on the metal organic framework 101 for a physical process, and the amine group of the polyetheramine 104 reacts with the hydroxyl group of the metal organic framework 101 for a dehydration reaction, and the pore size of the metal organic framework 101 is changed by the change of the external temperature. The grafting of the polyetheramine 104 on the metal organic framework 101 is a chemical reaction. The amine group of the polyetheramine 104 reacts with the hydroxyl group of the metal organic framework 101 for a dehydration reaction. The polyetheramine 104 is dehydrated to form a monoamino group 111 and a corresponding polyetheramine (monoamine group) modified zirconium hydroxyphthalate coated ionic liquid system 114; a diamino group 112 and a corresponding polyetheramine (diamine group) modified zirconium hydroxyphthalate coated ionic liquid system 115; and a triamino group 113 and a corresponding polyetheramine (triamine group) modified zirconium hydroxyphthalate coated ionic liquid system 116. Furthermore, in step S20, the oil bath heating condition is 50-80°C, and the oil bath heating stirring time is 8-16 hours.
[0021] By setting the heating conditions at 50~80°C and the oil bath heating stirring time at 8~16 hours, it is possible to better observe the solubility of the polyether amine modified metal organic framework coated ionic liquid system 106 under the influence of stirring time and heating temperature, and optimize the operating conditions to achieve the purpose of preparing a uniform and dense mixed matrix membrane.
[0022] Furthermore, in step S20, the vacuum pressure of the room temperature vacuum treatment is between 0.01-0.02 MPa, and the vacuuming time is between 20-24 hours.
[0023] By setting the vacuum pressure of room temperature vacuum treatment between 0.01-0.02Mpa and the vacuuming time between 20-24h, the plasticizing effect of carbon dioxide 107 in the air on the casting liquid during film formation can be better reduced, and long-term vacuum can better remove the solvent inside the casting liquid and the gas molecules adsorbed on the surface.
[0024] like Figure 4 As shown, further, when the mixed matrix membrane is used for a mixed gas containing carbon dioxide 107, the transmembrane pressure difference of the mixed matrix membrane is required to be 0.1-0.5 MPa, the operating temperature is 30-60° C., and the separation method is: Place the mixed matrix membrane in the membrane device 10, adjust the thermostat 9 to the temperature required for the experiment, the operating temperature range can be selected from 30 to 60 ° C, adjust the pressure to the pressure required for the experiment, the operating pressure range can be selected from 0.1 to 0.5 MPa, first open the control valve 7 of the nitrogen cylinder 2 for pre-pressing for 60 minutes, until the digital pressure gauge 8 shows a stable reading, observe the increase in the reading of the bubble flowmeter 12 downstream of the membrane in a unit time, and calculate the nitrogen permeation flux, then open the methane cylinder 3 for pre-pressing for 60 minutes, ensure that all nitrogen is removed and the methane is pre-pressed on the membrane, observe the increase in the reading of the bubble flowmeter 12 downstream of the membrane in a unit time, and calculate the methane permeation flux. Secondly, open the oxygen cylinder 4 for pre-pressing for 60 minutes, ensure that all methane is removed and the oxygen is pre-pressed on the membrane, observe the increase in the reading of the bubble flowmeter 12 downstream of the membrane in a unit time, and calculate the oxygen permeation flux. Finally, open the carbon dioxide 107 gas cylinder 1 for pre-pressurization for 60 minutes to ensure that all oxygen is removed and the carbon dioxide 107 pre-pressurizes the membrane, and then observe the increase in the reading of the soap bubble flowmeter 12 downstream of the membrane per unit time to calculate the permeation flux of carbon dioxide 107. After measuring the permeation flux of each gas, the selectivity of carbon dioxide 107 / nitrogen and carbon dioxide 107 / methane is obtained.
[0025] It should be noted that the above separation method is also provided with a pressure reducing valve 5, a needle valve 6 and a pressure relief valve 11 to ensure the safe operation of the pipeline.
[0026] Further, in step S10, the ionic liquid 102 is 1-butyl-3-methylimidazolium hexafluorophosphate; 1-octyl-3-methylimidazolium hexafluorophosphate; 1-butyl-3-methylimidazolium tetrafluoroborate; 1-octyl-3-methylimidazolium tetrafluoroborate; The polyetheramine 104 is any one of polyetheramine 104M1000, polyetheramine 104M600, polyetheramine 104M2070, polyetheramine 104D2000, polyetheramine 104T5000 and polyetheramine 104T403.
[0027] Furthermore, in step S20, the mass fractions of the polyetheramine modified metal organic framework coated ionic liquid system 106 are 0, 1%, 2%, 3%, 4%, and 5%, respectively.
[0028] According to the above, in order to verify the selectivity of carbon dioxide 107 / nitrogen and carbon dioxide 107 / methane obtained by the above-mentioned different types of ionic liquids 102, polyetheramines 104 and polyetheramine-modified metal organic framework-encapsulated ionic liquid systems 109, this embodiment provides the following examples: Embodiment 1 (1) Specific synthesis method of zirconium hydroxyphthalate metal organic framework 101: Weigh 0.1258g of zirconium tetrachloride and dissolve it in a mixed solution of N, N-dimethylformamide / concentrated hydrochloric acid (12mL, 10:2, v / v) to obtain a uniform solution under stirring. At the same time, dissolve 2-hydroxyterephthalic acid (0.099g) in 10mL N, N-dimethylformamide, mix well, stir for 30 minutes, transfer to a polytetrafluoroethylene liner, and react at 80°C for 12 hours. After taking out, centrifuge and filter at a centrifuge speed of 8000 rpm. After centrifugation for 5 minutes, wash it three times with N, N-dimethylformamide to remove unreacted solutes, then wash it three times with ethanol to replace N, N-dimethylformamide, and finally dry the synthesized sample in an oven at 60°C for 12 hours to obtain a light green powder.
[0029] (2) The specific configuration method of the ionic liquid coated with the zirconium hydroxyphthalate metal organic framework 101 is: 1g of zirconium hydroxyphthalate metal organic framework 101 powder was added to 15g of anhydrous ethanol and stirred for about 4 hours. A film was covered on the glass beaker to prevent ethanol evaporation during stirring. Then 1g of ionic liquid was mixed into the zirconium hydroxyphthalate metal organic framework 101 solution, and then stirred in an 80℃ constant temperature oil bath for 4 hours. After cooling to room temperature, the obtained sample was washed 3 times with N, N-dimethylformamide, and then placed in an oven at 40℃ for 24 hours to obtain a light green powder.
[0030] (3) Preparation of polyetheramine 104 modified zirconium hydroxyphthalate metal organic framework coated ionic liquid: 1 g of hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was dissolved in ethanol and water (10 g, 70:30, wt%) solution, and then ultrasonicated for 2 hours. Then, polyetheramine 104D2000 was diluted to 15 wt% with ethanol and deionized water, and stirred for 1 hour. All substances were blended at 70 ° C for 30 hours with continuous stirring. After that, the polymer solution was filtered with a dialysis tube (7000 MWCO). Finally, the prepared polyetheramine 104D2000 modified hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was stored in a vacuum oven at 50 ° C for at least 60 hours to remove excess ethanol and deionized water.
[0031] (4) Preparation of mixed matrix membranes and their application in CO2-107 gas separation Weigh 1g of polyether block amide 105 (Pebax-1657) as the solute, ethanol and water (70:30, wt%) as the solvent, and seal them in a three-necked flask after dissolving them. Place them in a heat-collecting constant temperature heating magnetic stirrer, and reflux and stir them in an oil bath at 80°C for 4 hours to uniformly dissolve the polyether block amide 105 (Pebax-1657) in the mixed solution. After the operation is completed, a transparent homogeneous solution is obtained. A certain mass fraction of the prepared polyetheramine 104D2000 modified zirconium hydroxyphthalate metal organic framework 101 coated ionic liquid was added into a uniform solution of polyether block amide 105 (Pebax-1657), the temperature was adjusted from 80°C to 50°C, and refluxed with stirring for 8 hours; the stirred casting liquid was cooled to room temperature and allowed to stand for degassing for 24 hours; the casting liquid was poured onto a polytetrafluoroethylene plate by a casting method, and it was ensured to be evenly distributed on the entire polytetrafluoroethylene plate, and placed in a vacuum drying oven at room temperature for 20 hours, and then vacuum dried at 40°C for 4 hours to remove the residual solvent, and finally mixed matrix membranes with different contents were obtained.
[0032] Under the test conditions of 0.1 MPa and 40 °C, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, the filler content is 1wt%, and the permeation flux of carbon dioxide 107 is 85.56 Barrer (1 Barrer = 10 -10 cm 3 (STP)cm / cm 2 scmHg), the carbon dioxide 107 / nitrogen selectivity is 71.61, the carbon dioxide 107 / methane selectivity is 65.82, and the carbon dioxide 107 / oxygen selectivity is 37.69.
[0033] Under the experimental conditions of 0.1MPa and 40℃, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, the filler content is 2wt%, the permeation flux of carbon dioxide 107 is 94.86 Barrer, the carbon dioxide 107 / nitrogen selectivity is 79.05, the carbon dioxide 107 / methane selectivity is 67.75, and the carbon dioxide 107 / oxygen selectivity is 41.61.
[0034] Under the experimental conditions of 0.1MPa and 40℃, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, the filler content is 3wt%, the permeation flux of carbon dioxide 107 is 98.75 Barrer, the carbon dioxide 107 / nitrogen selectivity is 82.62, the carbon dioxide 107 / methane selectivity is 70.53, and the carbon dioxide 107 / oxygen selectivity is 43.48.
[0035] Under the experimental conditions of 0.1MPa and 40℃, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, the filler content is 4wt%, the permeation flux of carbon dioxide 107 is 83.8 Barrer, the carbon dioxide 107 / nitrogen selectivity is 68.31, the carbon dioxide 107 / methane selectivity is 59.86, and the carbon dioxide 107 / oxygen selectivity is 35.95.
[0036] Under the experimental conditions of 0.1MPa and 40℃, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, the filler content is 5wt%, the permeation flux of carbon dioxide 107 is 78.66 Barrer, the carbon dioxide 107 / nitrogen selectivity is 61.45, the carbon dioxide 107 / methane selectivity is 56.19, and the carbon dioxide 107 / oxygen selectivity is 29.34.
[0037] Example 2 (1) Specific synthesis method of zirconium hydroxyphthalate metal organic framework 101: Weigh 0.1258g of zirconium tetrachloride and dissolve it in a mixed solution of N, N-dimethylformamide / concentrated hydrochloric acid (12mL, 10:2, v / v) to obtain a uniform solution under stirring. At the same time, dissolve 2-hydroxyterephthalic acid (0.099g) in 10mL N, N-dimethylformamide, mix well, stir for 30 minutes, transfer to a polytetrafluoroethylene liner, and react at 80°C for 12 hours. After taking out, centrifuge and filter at a centrifuge speed of 8000 rpm. After centrifugation for 5 minutes, wash it three times with N, N-dimethylformamide to remove unreacted solutes, then wash it three times with ethanol to replace N, N-dimethylformamide, and finally dry the synthesized sample in an oven at 60°C for 12 hours to obtain a light green powder.
[0038] (2) The specific configuration method of the ionic liquid coated with the zirconium hydroxyphthalate metal organic framework 101 is: 1g of zirconium hydroxyphthalate metal organic framework 101 powder was added to 15g of anhydrous ethanol and stirred for about 4 hours. A film was covered on the glass beaker to prevent ethanol evaporation during stirring. Then 1g of ionic liquid was mixed into the zirconium hydroxyphthalate metal organic framework 101 solution, and then stirred in an 80℃ constant temperature oil bath for 4 hours. After cooling to room temperature, the obtained sample was washed 3 times with N, N-dimethylformamide, and then placed in an oven at 40℃ for 24 hours to obtain a light green powder.
[0039] (3) Preparation of polyetheramine 104-modified zirconium hydroxyphthalate metal organic framework 101 coated with ionic liquid: 1 g of hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was dissolved in ethanol and water (10 g, 70:30, wt%) solution, and then ultrasonicated for 2 hours. Then, polyetheramine 104D2000 was diluted to 15 wt% with ethanol and deionized water, and stirred for 1 hour. All substances were blended at 70 ° C for 30 hours with continuous stirring. After that, the polymer solution was filtered with a dialysis tube (7000 MWCO). Finally, the prepared polyetheramine 104D2000 modified hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was stored in a vacuum oven at 50 ° C for at least 60 hours to remove excess ethanol and deionized water.
[0040] (4) Preparation of mixed matrix membranes and their application in CO2-107 gas separation Weigh 1g of polyether block amide 105 (Pebax-1657) as the solute, ethanol and water (70:30, wt%) as the solvent, and seal them in a three-necked flask after dissolving them. Place them in a heat-collecting constant temperature heating magnetic stirrer, and reflux and stir them in an oil bath at 80°C for 4 hours to uniformly dissolve the polyether block amide 105 (Pebax-1657) in the mixed solution. After the operation is completed, a transparent homogeneous solution is obtained. A certain mass fraction of the prepared polyetheramine 104D2000 modified zirconium hydroxyphthalate metal organic framework 101 coated ionic liquid was added to a uniform solution of polyether block amide 105 (Pebax-1657), the temperature was adjusted from 80°C to 50°C, and refluxed with stirring for 8 hours; the stirred casting liquid was cooled to room temperature and allowed to stand for degassing for 24 hours; the casting liquid was poured onto a polytetrafluoroethylene plate by a casting method, and it was ensured to be evenly distributed on the entire polytetrafluoroethylene plate, and placed in a vacuum drying oven at room temperature for 20 hours, and then vacuum dried at 40°C for 4 hours to remove the residual solvent, and finally a mixed matrix membrane with a filler content of 3wt% was obtained.
[0041] Under the experimental conditions of 0.2MPa and 30℃, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, the permeation flux of carbon dioxide 107 is 104.56 Barrer, the carbon dioxide 107 / nitrogen selectivity is 85.13, the carbon dioxide 107 / methane selectivity is 74.68, and the carbon dioxide 107 / oxygen selectivity is 44.81.
[0042] Under the experimental conditions of 0.3 MPa and 30°C, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, the permeation flux of carbon dioxide 107 is 109.12 Barrer, the carbon dioxide 107 / nitrogen selectivity is 77.94, the carbon dioxide 107 / methane selectivity is 77.94, and the carbon dioxide 107 / oxygen selectivity is 46.5.
[0043] Under the experimental conditions of 0.4 MPa and 30°C, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, the permeation flux of carbon dioxide 107 is 115.48 Barrer, the carbon dioxide 107 / nitrogen selectivity is 82.48, the carbon dioxide 107 / methane selectivity is 82.48, and the carbon dioxide 107 / oxygen selectivity is 50.51.
[0044] Under the experimental conditions of 0.5 MPa and 30°C, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, the permeation flux of carbon dioxide 107 is 119.85 Barrer, the carbon dioxide 107 / nitrogen selectivity is 85.61, the carbon dioxide 107 / methane selectivity is 85.61, and the carbon dioxide 107 / oxygen selectivity is 57.21.
[0045] Example 3 (1) Specific synthesis method of zirconium hydroxyphthalate metal organic framework 101: Weigh 0.1258g of zirconium tetrachloride and dissolve it in a mixed solution of N, N-dimethylformamide / concentrated hydrochloric acid (12mL, 10:2, v / v) to obtain a uniform solution under stirring. At the same time, dissolve 2-hydroxyterephthalic acid (0.099g) in 10mL N, N-dimethylformamide, mix well, stir for 30 minutes, transfer to a polytetrafluoroethylene liner, and react at 80°C for 12 hours. After taking out, centrifuge and filter at a centrifuge speed of 8000 rpm. After centrifugation for 5 minutes, wash it three times with N, N-dimethylformamide to remove unreacted solutes, then wash it three times with ethanol to replace N, N-dimethylformamide, and finally dry the synthesized sample in an oven at 60°C for 12 hours to obtain a light green powder.
[0046] (2) The specific configuration method of the ionic liquid coated with the zirconium hydroxyphthalate metal organic framework 101 is: 1g of zirconium hydroxyphthalate metal organic framework 101 powder was added to 15g of anhydrous ethanol and stirred for about 4 hours. A film was covered on the glass beaker to prevent ethanol evaporation during stirring. Then 1g of ionic liquid was mixed into the zirconium hydroxyphthalate metal organic framework 101 solution, and then stirred in an 80℃ constant temperature oil bath for 4 hours. After cooling to room temperature, the obtained sample was washed 3 times with N, N-dimethylformamide, and then placed in an oven at 40℃ for 24 hours to obtain a light green powder.
[0047] (3) Preparation of polyetheramine 104-modified zirconium hydroxyphthalate metal organic framework 101 coated with ionic liquid: 1 g of hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was dissolved in ethanol and water (10 g, 70:30, wt%) solution, and then ultrasonicated for 2 hours. Then, polyetheramine 104D2000 was diluted to 15 wt% with ethanol and deionized water, and stirred for 1 hour. All substances were blended at 70 ° C for 30 hours with continuous stirring. After that, the polymer solution was filtered with a dialysis tube (7000 MWCO). Finally, the prepared polyetheramine 104D2000 modified hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was stored in a vacuum oven at 50 ° C for at least 60 hours to remove excess ethanol and deionized water.
[0048] (4) Preparation of mixed matrix membranes and their application in CO2-107 gas separation 1 g of polyether block amide 105 (Pebax-1657) was weighed as a solute using an electronic balance, and ethanol and water (70:30, wt%) were used as solvents. The two were dissolved and sealed in a three-necked flask, placed in a heat-collecting constant temperature heating magnetic stirrer, and refluxed and stirred at 80°C in an oil bath for 4 hours to uniformly dissolve the polyether block amide 105 (Pebax-1657) in the mixed solution. A transparent homogeneous solution was obtained after the operation was completed. A certain mass fraction of the prepared polyetheramine 104D2000 modified zirconium hydroxyphthalate metal organic framework 101 coated ionic liquid was added to a uniform solution of polyether block amide 105 (Pebax-1657), the temperature was adjusted from 80°C to 50°C, and refluxed with stirring for 8 hours; the stirred casting liquid was cooled to room temperature and allowed to stand for degassing for 24 hours; the casting liquid was poured onto a polytetrafluoroethylene plate by a casting method, and it was ensured to be evenly distributed on the entire polytetrafluoroethylene plate, and placed in a vacuum drying oven at room temperature for 20 hours, and then vacuum dried at 40°C for 4 hours to remove the residual solvent, and finally a mixed matrix membrane with a filler content of 1wt% was obtained.
[0049] Under the experimental conditions of 0.2MPa and 50℃, the ionic liquid is 1-octyl-3-methylimidazolium hexafluorophosphate, the permeation flux of carbon dioxide 107 is 86.26 Barrer, the carbon dioxide 107 / nitrogen selectivity is 78.72, the carbon dioxide 107 / methane selectivity is 66.35, and the carbon dioxide 107 / oxygen selectivity is 37.49.
[0050] Under the experimental conditions of 0.2MPa and 50℃, the ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate, the permeation flux of carbon dioxide 107 is 79.82 Barrer, the carbon dioxide 107 / nitrogen selectivity is 64.58, the carbon dioxide 107 / methane selectivity is 59.12, and the carbon dioxide 107 / oxygen selectivity is 30.75.
[0051] Under the experimental conditions of 0.2MPa and 50℃, the ionic liquid is 1-octyl-3-methylimidazolium tetrafluoroborate, the permeation flux of carbon dioxide 107 is 70.09 Barrer, the carbon dioxide 107 / nitrogen selectivity is 55.09, the carbon dioxide 107 / methane selectivity is 48.34, and the carbon dioxide 107 / oxygen selectivity is 26.23.
[0052] Example 4 The zirconium hydroxyphthalate metal organic framework 101 prepared in Example 1 (1) and the zirconium hydroxyphthalate metal organic framework 101 prepared in Example 1 (2) are used to coat the ionic liquid.
[0053] The polyetheramine 104D2000 in Example 1 (3) was replaced with polyetheramine 104M2070.
[0054] (3) Preparation of polyetheramine 104-modified zirconium hydroxyphthalate metal organic framework 101 coated with ionic liquid: 1 g of hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was dissolved in ethanol and water (10 g, 70:30, wt%) solution, and then ultrasonicated for 2 hours. Then, polyetheramine 104M2070 was diluted to 15 wt% with ethanol and deionized water and stirred for 1 hour. All substances were blended at 70 ° C for 30 hours with continuous stirring. After that, the polymer solution was filtered with a dialysis tube (7000 MWCO). Finally, the prepared polyetheramine 104M2070 modified hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was stored in a vacuum oven at 50 ° C for at least 60 hours to remove excess ethanol and deionized water.
[0055] (4) Preparation of mixed matrix membranes and their application in CO2-107 gas separation 1 g of polyether block amide 105 (Pebax-1657) was weighed as a solute using an electronic balance, and ethanol and water (70:30, wt%) were used as solvents. The two were dissolved and sealed in a three-necked flask, placed in a heat-collecting constant temperature heating magnetic stirrer, and refluxed and stirred at 80°C in an oil bath for 4 hours to uniformly dissolve the polyether block amide 105 (Pebax-1657) in the mixed solution. A transparent homogeneous solution was obtained after the operation was completed. A certain mass fraction of the prepared polyetheramine 104M2070 modified zirconium hydroxyphthalate metal organic framework 101 coated ionic liquid was added to a uniform solution of polyether block amide 105 (Pebax-1657), the temperature was adjusted from 80°C to 50°C, and refluxed with stirring for 8 hours; the stirred casting liquid was cooled to room temperature and allowed to stand for degassing for 24 hours; the casting liquid was poured onto a polytetrafluoroethylene plate by a casting method, and it was ensured to be evenly distributed on the entire polytetrafluoroethylene plate, and placed in a vacuum drying oven at room temperature for 20 hours, and then vacuum dried at 40°C for 4 hours to remove the residual solvent, and finally a mixed matrix membrane with a filler content of 4wt% was obtained.
[0056] Under the experimental conditions of 0.5 MPa and 40°C, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, the permeation flux of carbon dioxide 107 is 117.91 Barrer, the carbon dioxide 107 / nitrogen selectivity is 93.37, the carbon dioxide 107 / methane selectivity is 87.34, and the carbon dioxide 107 / oxygen selectivity is 30.75.
[0057] Under the experimental conditions of 0.5 MPa and 40°C, the ionic liquid is 1-octyl-3-methylimidazolium hexafluorophosphate, the permeation flux of carbon dioxide 107 is 113.08 Barrer, the carbon dioxide 107 / nitrogen selectivity is 91.59, the carbon dioxide 107 / methane selectivity is 84.39, and the carbon dioxide 107 / oxygen selectivity is 26.23.
[0058] Under the experimental conditions of 0.5 MPa and 40°C, the ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate, the permeation flux of carbon dioxide 107 is 115.96 Barrer, the carbon dioxide 107 / nitrogen selectivity is 94.97, the carbon dioxide 107 / methane selectivity is 86.54, and the carbon dioxide 107 / oxygen selectivity is 49.14.
[0059] Under the experimental conditions of 0.5MPa and 40℃, the ionic liquid is 1-octyl-3-methylimidazolium tetrafluoroborate, the permeation flux of carbon dioxide 107 is 114.72 Barrer, the carbon dioxide 107 / nitrogen selectivity is 92.37, the carbon dioxide 107 / methane selectivity is 85.61, and the carbon dioxide 107 / oxygen selectivity is 48.62.
[0060] Example 5 The zirconium hydroxyphthalate metal organic framework 101 prepared in Example 1 (1) was used.
[0061] The ionic liquid of Example 1 (2) was fixed to 1-octyl-3-methylimidazolium hexafluorophosphate; the polyetheramine 104 of Example 1 (3) was changed to polyetheramine 104 (M1000, T5000, T403, M600) (3) Preparation of polyetheramine 104-modified zirconium hydroxyphthalate metal organic framework 101 coated with ionic liquid: 1 g of hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was dissolved in ethanol and water (10 g, 70:30, wt%) solution, and then ultrasonicated for 2 h. Then, polyetheramine 104 was diluted to 15 wt% with ethanol and deionized water and stirred for 1 h. All materials were blended at 70 °C for 30 h with constant stirring. After that, the polymer solution was filtered with a dialysis tube (7000 MWCO for M1000, 14000 MWCO for T5000, and 3500 MWCO for T403 and M600). Finally, the prepared polyetheramine 104 modified hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was stored in a vacuum oven at 50 °C for at least 60 h to remove excess ethanol and deionized water.
[0062] (4) Preparation of mixed matrix membranes and their application in CO2-107 gas separation 1 g of polyether block amide 105 (Pebax-1657) was weighed as a solute using an electronic balance, and ethanol and water (70:30, wt%) were used as solvents. The two were dissolved and sealed in a three-necked flask, placed in a heat-collecting constant temperature heating magnetic stirrer, and refluxed and stirred at 80°C in an oil bath for 4 hours to uniformly dissolve the polyether block amide 105 (Pebax-1657) in the mixed solution. A transparent homogeneous solution was obtained after the operation was completed. A certain mass fraction of the prepared polyetheramine 104-modified zirconium hydroxyphthalate metal organic framework 101 coated ionic liquid was added to a uniform solution of polyether block amide 105 (Pebax-1657), the temperature was adjusted from 80°C to 50°C, and refluxed with stirring for 8 hours; the stirred casting liquid was cooled to room temperature and allowed to stand for degassing for 24 hours; the casting liquid was poured onto a polytetrafluoroethylene plate by a casting method, and it was ensured to be evenly distributed on the entire polytetrafluoroethylene plate, and placed in a vacuum drying oven at room temperature for 20 hours, and then vacuum dried at 40°C for 4 hours to remove the residual solvent, and finally a mixed matrix membrane with a filler content of 3wt% was obtained.
[0063] Under the test conditions of 0.2 MPa and 40°C, the polyetheramine 104 is polyetheramine 104M1000, the permeation flux of carbon dioxide 107 is 91.59 Barrer, the carbon dioxide 107 / nitrogen selectivity is 86.26, the carbon dioxide 107 / methane selectivity is 79.64, and the carbon dioxide 107 / oxygen selectivity is 45.5.
[0064] Under the test conditions of 0.2 MPa and 40°C, the polyetheramine 104 is polyetheramine 104M600, the permeation flux of carbon dioxide 107 is 65.32 Barrer, the carbon dioxide 107 / nitrogen selectivity is 55.4, the carbon dioxide 107 / methane selectivity is 52.36, and the carbon dioxide 107 / oxygen selectivity is 29.16.
[0065] Under the test conditions of 0.2 MPa and 40°C, the polyetheramine 104 is polyetheramine 104T5000, the permeation flux of carbon dioxide 107 is 89.75 Barrer, the carbon dioxide 107 / nitrogen selectivity is 87.58, the carbon dioxide 107 / methane selectivity is 72.96, and the carbon dioxide 107 / oxygen selectivity is 46.09.
[0066] Under the test conditions of 0.2 MPa and 40°C, the polyetheramine 104 is polyetheramine 104T403, the permeation flux of carbon dioxide 107 is 67.61 Barrer, the carbon dioxide 107 / nitrogen selectivity is 59.92, the carbon dioxide 107 / methane selectivity is 56.34, and the carbon dioxide 107 / oxygen selectivity is 27.23.
[0067] Example 6 The zirconium hydroxyphthalate metal organic framework 101 prepared in Example 1 (1) and the zirconium hydroxyphthalate metal organic framework 101 prepared in Example 1 (2) are used to coat the ionic liquid.
[0068] The polyetheramine 104D2000 in Example 1 (3) was replaced with polyetheramine 104M1000.
[0069] (3) Preparation of ionic liquid coated on polyetheramine 104-modified zirconium hydroxyphthalate metal organic framework 101: 1 g of hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was dissolved in ethanol and water (10 g, 70:30, wt%) solution, and then ultrasonicated for 2 hours. Then, polyetheramine 104M1000 was diluted to 15 wt% with ethanol and deionized water and stirred for 1 hour. All substances were blended at 70 ° C for 30 hours with continuous stirring. After that, the polymer solution was filtered with a dialysis tube (7000 MWCO). Finally, the prepared polyetheramine 104M1000 modified hydroxyphthalic acid zirconium metal organic framework 101 coated ionic liquid was stored in a vacuum oven at 50 ° C for at least 60 hours to remove excess ethanol and deionized water.
[0070] (4) Preparation of mixed matrix membranes and their application in CO2-107 gas separation 1 g of polyether block amide 105 (Pebax-1657) was weighed as a solute using an electronic balance, and ethanol and water (70:30, wt%) were used as solvents. The two were dissolved and sealed in a three-necked flask, placed in a heat-collecting constant temperature heating magnetic stirrer, and refluxed and stirred at 80°C in an oil bath for 4 hours to uniformly dissolve the polyether block amide 105 (Pebax-1657) in the mixed solution. A transparent homogeneous solution was obtained after the operation was completed. A certain mass fraction of the prepared polyetheramine 104M1000 modified zirconium hydroxyphthalate metal organic framework 101 coated ionic liquid was added to a uniform solution of polyether block amide 105 (Pebax-1657), the temperature was adjusted from 80°C to 50°C, and refluxed with stirring for 8 hours; the stirred casting liquid was cooled to room temperature, and allowed to stand for degassing for 24 hours; the casting liquid was poured onto a polyfluoro plate by a casting method, and it was ensured to be evenly distributed on the entire polyfluoro plate, and placed in a vacuum drying oven at room temperature for 20 hours, and then vacuum dried at 40°C for 4 hours to remove the residual solvent, and finally a mixed matrix membrane with a filler content of 5wt% was obtained.
[0071] Under the experimental conditions of 0.3MPa and 60℃, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate, the permeation flux of carbon dioxide 107 is 105.7 Barrer, the carbon dioxide 107 / nitrogen selectivity is 54.63, the carbon dioxide 107 / methane selectivity is 48.04, and the carbon dioxide 107 / oxygen selectivity is 28.75.
[0072] Under the experimental conditions of 0.3MPa and 60℃, the ionic liquid is 1-octyl-3-methylimidazolium hexafluorophosphate, the permeation flux of carbon dioxide 107 is 92.36 Barrer, the carbon dioxide 107 / nitrogen selectivity is 40.58, the carbon dioxide 107 / methane selectivity is 36.94, and the carbon dioxide 107 / oxygen selectivity is 21.36.
[0073] Under the experimental conditions of 0.3 MPa and 60°C, the ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate, the permeation flux of carbon dioxide 107 is 81.05 Barrer, the carbon dioxide 107 / nitrogen selectivity is 39.67, the carbon dioxide 107 / methane selectivity is 36.84, and the carbon dioxide 107 / oxygen selectivity is 20.88.
[0074] Under the experimental conditions of 0.3MPa and 60℃, the ionic liquid is 1-octyl-3-methylimidazolium tetrafluoroborate, the permeation flux of carbon dioxide 107 is 70.87 Barrer, the carbon dioxide 107 / nitrogen selectivity is 35.11, the carbon dioxide 107 / methane selectivity is 32.21, and the carbon dioxide 107 / oxygen selectivity is 18.47.
[0075] like Figure 3 As shown above, it can be seen that the separation performance of the mixed matrix membrane has significantly exceeded the Robeson upper limit in 2008, indicating that the separation performance of the mixed matrix membrane meets the commercial needs of the technology.
[0076] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a porous liquid mixed matrix membrane and its application, characterized in that: The steps include: S10. Utilizing the property that the metal organic framework can adjust the pore size under the influence of temperature, the ionic liquid is coated on the metal organic framework under the action of the first temperature, and then the polyetheramine is grafted on the surface of the metal organic framework in a weakly alkaline environment to form a polyetheramine-modified metal organic framework coated with an ionic liquid system having a core-shell structure; S20. The polyetheramine-modified metal organic framework-coated ionic liquid system obtained in step S10 is added to the polyether block amide to obtain a casting solution, and then heated and stirred in an oil bath; The uniformly stirred casting solution is poured into a polytetrafluoroethylene plate by a casting method, and after vacuum treatment at room temperature and heating degassing, a required mixed matrix membrane containing polyetheramine-modified metal organic framework-coated ionic liquid and polyether block amide is obtained.
2. The method for preparing and using the porous liquid mixed matrix membrane according to claim 1, characterized in that: In step S10, the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate; 1-octyl-3-methylimidazolium hexafluorophosphate; 1-butyl-3-methylimidazolium tetrafluoroborate; 1-octyl-3-methylimidazolium tetrafluoroborate; The metal organic framework is a zirconium hydroxyphthalate metal organic framework; and the ionic liquid is coated on the metal organic framework to form a zirconium hydroxyphthalate coated ionic liquid system; The polyetheramine is any one of polyetheramine M1000, polyetheramine M600, polyetheramine M2070, polyetheramine D2000, polyetheramine T5000 and polyetheramine T403.
3. The method for preparing and using the porous liquid mixed matrix membrane according to claim 1, characterized in that: In step S20, the mass fractions of the polyetheramine modified metal organic framework-coated ionic liquid system are 0, 1%, 2%, 3%, 4%, and 5%, respectively.
4. The method for preparing and using the porous liquid mixed matrix membrane according to claim 1, characterized in that: In step S20, the oil bath heating condition is 50-80°C, and the oil bath heating stirring time is 8-16 hours.
5. The method for preparing and using the porous liquid mixed matrix membrane according to claim 1, characterized in that: In step S20, the vacuum pressure of the room temperature vacuum treatment is between 0.01-0.02 MPa, and the vacuuming time is between 20-24 hours.
6. The method for preparing and using the porous liquid mixed matrix membrane according to claim 1, characterized in that: When the mixed matrix membrane is used for a mixed gas containing carbon dioxide, the transmembrane pressure difference of the mixed matrix membrane is required to be 0.1~0.5Mpa and the operating temperature is required to be 30~60℃.
Citation Information
Patent Citations
Polyether block amide / polyion liquid semi-interpenetrating polymer network film and thermosetting preparation method thereof
CN103665403A
Preparation method and application of ionic liquid blended membrane
CN105749769A
Mixed matrix membrane filled with ionic liquid-hollow polyhedron and preparation method and application
CN109663512A
Preparation method of MOF-based mixed matrix ionic gel film
CN116272437A
Method for preparing mixed matrix membrane from modified metal organic framework and mixed matrix membrane
CN117815925A